Viral infectious diseases severity: co-presence of transcriptionally active microbes (TAMs) can play an integral role for disease severity - Yadav, Aanchal; Pandey, Rajesh (Frontiers in Immunology, 2022)
Humans have been challenged by infectious diseases for all of their recorded history, and are continually being affected even today. Next-generation sequencing (NGS) has enabled identification of, i) culture independent microbes, ii) emerging disease-causing pathogens, and iii) understanding of the genome architecture. This, in turn, has highlighted that pathogen/s are not a monolith, and thereby allowing for the differentiation of the wide-ranging disease symptoms, albeit infected by a primary pathogen. The conventional ‘one disease - one pathogen’ paradigm has been positively revisited by considering limited yet important evidence of the co-presence of multiple transcriptionally active microbes (TAMs), potential pathogens, in various infectious diseases, including the COVID-19 pandemic. The ubiquitous microbiota presence inside humans gives reason to hypothesize that the microbiome, especially TAMs, contributes to disease etiology. Herein, we discuss current evidence and inferences on the co-infecting microbes particularly in the diseases caused by the RNA viruses - Influenza, Dengue, and the SARS-CoV-2. We have highlighted that the specific alterations in the microbial taxonomic abundances (dysbiosis) is functionally connected to the exposure of primary infecting pathogen/s. The microbial presence is intertwined with the differential host immune response modulating differential disease trajectories. The microbiota-host interactions have been shown to modulate the host immune responses to Influenza and SARS-CoV-2 infection, wherein the active commensal microbes are involved in the generation of virus-specific CD4 and CD8 T-cells following the influenza virus infection. Furthermore, COVID-19 dysbiosis causes an increase in inflammatory cytokines such as IL-6, TNF-α, and IL-1β, which might be one of the important predisposing factors for severe infection. Through this article, we aim to provide a comprehensive view of functional microbiomes that can have a significant regulatory impact on predicting disease severity (mild, moderate and severe), as well as clinical outcome (survival and mortality). This can offer fresh perspectives on the novel microbial biomarkers for stratifying patients for severe disease symptoms, disease prevention and augmenting treatment regimens.